Poland's Energy Transition from 2015 to 2020 in the International Perspective - Bajołek, Paweł; Król, Michał (Journal of Public Governance, 2023)
Objective: This paper discusses a new composite indicator illustrating Poland’s energy transition from 2015 to 2020. Specifically, it addresses the following research questions: 1. How did energy transition in Poland evolve between 2015 and 2020?; 2. How did Poland’s energy transition efforts compare with those of the other EU countries before the energy crisis?; 3. What internal factors limited Poland’s capacity for energy transition between 2015 and 2020?Research Design & Methods: The analysis is based on existing data for 2015‒2020 downloaded from the Eurostat database. Selected indicators were divided into four categories and normalised, as well as stimulants and destimulants were determined to obtain composite indicators for individual countries.Findings: 1. For 2020, Poland had the lowest score (‒26.92) among 22 EU countries on the new indicator. 2. From 2015 to 2019, Poland ranked among the bottom three EU countries. 3. The structure of the energy mix had the greatest impact on the indicator.Implications/Recommendations: The composite indicator developed for the purpose of this study makes it easier to compare the energy transition process across the EU countries and demonstrates in which areas specific economies perform better or worse.Contribution/Value Added: The new indicator offers a somewhat different perspective on energy transition in the EU. Unlike other composite indicators in the literature, it focuses on four key areas of energy transition, i.e. economy, energy mix, energy prices, and import dependency.Article classification: research articleJEL classification: Q43, Q48